Cerebrospinal Fluid Levels of Chromogranin A in Parkinson's Disease and Multiple System Atrophy - Kaiserova, Michaela; Chudackova, Monika; Mensikova, Katerina; Vastik, Miroslav; Kurcova, Sandra; Prikrylova Vranova, Hana; Stejskal, David; Kanovsky, Petr (Brain sciences, 2021)
BACKGROUND: Chromogranin A (CgA) and other peptides from the chromogranin-secretogranin family have been recently studied as potential biomarkers of various neurodegenerative diseases, including Parkinson's disease (PD). METHODS: We measured CgA in the cerebrospinal fluid (CSF) of 119 PD patients, 18 multiple system atrophy (MSA) patients, and 31 age-matched controls. We also correlated the values with disease duration and levodopa dose equivalent. RESULTS: In the PD patients, CSF CgA tended to be lower than the control group (median 124.5 vs. 185.2 µg/L; p = 0.057); however, the results did not reach statistical significance. CSF CgA levels in MSA were significantly lower compared to the control group (median 104.4 vs. 185.2; p = 0.014). There was no significant difference in CSF CgA between PD and MSA patients (p = 0.372). There was no association between CSF CgA and disease duration or levodopa dose equivalent in PD or in MSA. CONCLUSIONS: We observed a tendency toward lower CSF CgA levels in both PD and MSA compared to the control group; however, the difference reached statistical significance only in MSA. Based on these results, CgA may have potential as a biomarker in PD and MSA, but further studies on larger numbers of patients are needed to draw conclusions.
Keywords: Parkinson’s disease; chromogranin A; multiple system atrophy; cerebrospinal fluid